1995
DOI: 10.1128/jvi.69.10.6063-6076.1995
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal repressor region of herpes simplex virus type 1 ICP27 is required for the redistribution of small nuclear ribonucleoprotein particles and splicing factor SC35; however, these alterations are not sufficient to inhibit host cell splicing

Abstract: Herpes simplex virus type 1 infection results in a reorganization of antigens associated with the small nuclear ribonucleoprotein particles (snRNPs), resulting in the formation of prominent clusters near the nuclear periphery. In this study, we show that the immediate-early protein ICP27, which is involved in the impairment of host cell splicing and in the changes in the distribution of snRNPs, is also required for reassorting the SR domain splicing factor SC35. Other viral processes, such as adsorption and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 72 publications
2
82
1
Order By: Relevance
“…ICP27 has many roles during the course of the HSV-1 replication cycle. In addition to being necessary for transcription of ␥1 and ␥2 viral genes (79), ICP27 regulates polyadenylation site selection (22,31,55), regulates the intranuclear distribution of splicing factors (52,82), interacts with the export factor Aly/Ref (13), shuttles between the nucleus and cytoplasm (60,69,87), and demonstrates RNA binding activity (59). These functions are consistent with a role of ICP27 in suppressing cellular posttranscriptional processing and transport while promoting viral transcription.…”
Section: Fig 2 Infection With Uv-irradiated Hsv Does Not Results In mentioning
confidence: 74%
“…ICP27 has many roles during the course of the HSV-1 replication cycle. In addition to being necessary for transcription of ␥1 and ␥2 viral genes (79), ICP27 regulates polyadenylation site selection (22,31,55), regulates the intranuclear distribution of splicing factors (52,82), interacts with the export factor Aly/Ref (13), shuttles between the nucleus and cytoplasm (60,69,87), and demonstrates RNA binding activity (59). These functions are consistent with a role of ICP27 in suppressing cellular posttranscriptional processing and transport while promoting viral transcription.…”
Section: Fig 2 Infection With Uv-irradiated Hsv Does Not Results In mentioning
confidence: 74%
“…Kaposi's sarcoma-associated herpesvirus (KSHV) ORF57 is an essential protein conserved amongst all herpesviruses [1][2][3][4][5][6][7][8][9][10][11]. It is a multi-functional regulator of gene expression assuming many roles during the course of infection, including transcriptional activation, enhancing viral splicing and viral mRNA accumulation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the nuclear speckles serve as storage sites for splicing factors, while splicing occurs on nascent transcripts (18,63,81). Splicing factors have been found to redistribute in response to transcription inhibition (9), splicing inhibition (19,46), and viral infection (5,8,13,28,37,49,53). During infection with herpes simplex virus type 1 (HSV-1), a dramatic redistribution of snRNPs and the SR protein SC35 from their normal speckled staining pattern occurs with the formation of prominent clusters, which appear to condense throughout the nucleus and then migrate to the nuclear periphery as infection proceeds (37,49,53).…”
mentioning
confidence: 99%
“…Splicing factors have been found to redistribute in response to transcription inhibition (9), splicing inhibition (19,46), and viral infection (5,8,13,28,37,49,53). During infection with herpes simplex virus type 1 (HSV-1), a dramatic redistribution of snRNPs and the SR protein SC35 from their normal speckled staining pattern occurs with the formation of prominent clusters, which appear to condense throughout the nucleus and then migrate to the nuclear periphery as infection proceeds (37,49,53). Furthermore, studies by Phelan et al (49) and in our laboratory (53) demonstrated that an HSV-1 immediate-early regulatory protein, ICP27 (IE63), was essential for the relocalization of the snRNPs and that ICP27 colocalized with the snRNPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation